2020
DOI: 10.2495/eq-v5-n1-48-59
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the development of the value of the mining-industrial heritage of the Zaruma-Portovelo, ecuador, in the context of a geopark project

Abstract: the enhancement of heritage resources helps to promote conservation, contributes to more significant and better protection, and favors the efficient use of these resources. Many heritage works and liabilities linked to mining activity are abandoned, causing the deterioration of heritage resources that may become environmental liabilities over time. this work aims to develop strategies for the development of the Mining-industrial heritages through participatory methods for geomining enhancement and development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…The analysis of the DIPS map in this study revealed areas with a high vulnerability that require strategies to promote the development and continuous improvement of the territory [127]. The following requirements should be met: (i) oil wells must have a surrounding security infrastructure; (ii) abandoned wells must have isolation and protection infrastructure; (iii) territorial reordering that considers the critical zones detected in this work should be proposed; (iv) the population must be made aware of the risks associ-ated with oil wells in the sector; and (v) new settlements in the vicinity of wells must be prevented.…”
Section: Discussionmentioning
confidence: 86%
“…The analysis of the DIPS map in this study revealed areas with a high vulnerability that require strategies to promote the development and continuous improvement of the territory [127]. The following requirements should be met: (i) oil wells must have a surrounding security infrastructure; (ii) abandoned wells must have isolation and protection infrastructure; (iii) territorial reordering that considers the critical zones detected in this work should be proposed; (iv) the population must be made aware of the risks associ-ated with oil wells in the sector; and (v) new settlements in the vicinity of wells must be prevented.…”
Section: Discussionmentioning
confidence: 86%
“…When referring to responsible mining as activity towards sustainable development, it is necessary to consider post-mining recovery, take advantage of mining exploitation areas, and promote sustainable tourism through thematic mining parks, underground museums, and touristic mines. It is essential to value geodiversity and rescue the geological and mining heritage [27][28][29].…”
Section: Defining Search Termsmentioning
confidence: 99%
“…The geopark includes urban and rural zones, where certain geosites have oil activity and natural hydrocarbon outcrops (bituminous oozes) [45]. Geosites help protecting the geoenvironment from anthropogenic actions, strengthening the geo-conservation of heritage sites (rural zone, Ancón) [46][47] and encouraging geotourism [48][49].…”
Section: Focus Group Technique Analysismentioning
confidence: 99%